Serotonin 5-HT7 receptor agents: Structure-activity relationships and potential therapeutic applications in central nervous system disorders - Leopoldo, Marcello; Lacivita, Enza; Berardi, Francesco; Perrone, Roberto; Hedlund, Peter B. (Pharmacology & therapeutics (Oxford), 2011)
Since its discovery in the 1940s in serum, the mammalian intestinal mucosa, and in the central nervous system, serotonin (5-HT) has been shown to be involved in virtually all cognitive and behavioral human functions, and alterations in its neurochemistry have been implicated in the etiology of a plethora of neuropsychiatric disorders. The cloning of 5-HT receptor subtypes has been of importance in enabling them to be classified as specific protein molecules encoded by specific genes. The 5-HT(7) receptor is the most recently classified member of the serotonin receptor family. Since its identification, it has been the subject of intense research efforts driven by its presence in functionally relevant regions of the brain. The availability of some selective antagonists and agonists, in combination with genetically modified mice lacking the 5-HT(7) receptor, has allowed for a better understanding of the pathophysiological role of this receptor. This paper reviews data on localization and pharmacological properties of the 5-HT(7) receptor, and summarizes the results of structure-activity relationship studies aimed at the discovery of selective 5-HT(7) receptor ligands. Additionally, an overview of the potential therapeutic applications of 5-HT(7) receptor agonists and antagonists in central nervous system disorders is presented.